Comparative study on the sedative effects of betadine 1% and eugenol in teeth of children ages 5-7 - Ramos, Tristan Nathaniel; Yap, Rael Viola; Estaniel, Cynthia (Adviser).; Ortiz, Georgiana (Adviser).
This is an experimental study on the effectivity of Betadine 1% (Povidone -Iodine) in the. sedation of children's teeth with acute and chronic pulpitis. The study was undertaken using the cross-over design wherein a total of 20 children from the East Riverside Day Care Center aged 5-7 were used as subjects. The subjects were randomly grouped. One group received Betadine 1% and the other, Eugenol. Hie results showed that Betadine 1% can even be more effective in sedating children's teeth in cases of acute or chronic pulpitis.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Sedatives; Anesthesia in dentistry